PENGARUH METODE TALKING STICK TERHADAP HASIL BELAJAR SISWA KELAS X MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK NU 01 JOGOROTO JOMBANG - Hana Al Fazila; Hasan, Zaenal Arifin (PAI FAI UNHASY Tebuireng Jombang, 2023)
In general, the center of the learning process is focusing on the teacher. In the process of increasing student learning success, the teacher has an important role. Usually the learning that occurs is that students sit and listen to what is conveyed by the teacher which makes the effectiveness of learning less. With this, a learning method is needed so that activeness returns to life. This article aims to find out the implementation, learning outcomes and the influence of the Talking Stick method on the learning outcomes of class X students in Islamic Religious Education Subject. This research belongs to the Quasi experimental One-Group Pretest Posttest Design with a quantitative approach. In collecting data using observations, tests, and photographs. The results of this study are 1). Implementation of this method goes well. Evidenced by the frequency distribution table, namely the frequency of 12 with intervals of 85-95 and a percentage of 46.15% is included in the good category. 2). In the experimental class, it was found that the mean pretest was 55.00 and 87.88 posttest. Meanwhile for the control class, the mean pretest score was 42.69 and posttest was 63.27. The learning output of class X students of PAI subjects at SMK NU 01 Jogoroto Jombang increased as an indicator of the mean value. 3). The calculation results of the paired sample t test using a 95% confidence level are known to be the value of Sig. (2tailed) is 0.000 (0.000 <0.05) which means that H0 is rejected and Ha is accepted.